The Influencing Factors of Acceptance of Disablility in Spinal Cord Injured Patients - Attawong, Tuenchai; Kovindha, Apichana (Nepal Journal of Neuroscience, 2005)
The objective of this study was to examine the psychological factors related to acceptance of disability and to compare the correlated factors with duration of spinal cord injury (SCI). Demographic data, the Acceptance of Disability Scale, the Hospital Anxiety and Depression Scale and the General Perceived Self-Efficacy Scale were analyzed to assess correlation with acceptance of disability of SCI persons attending the outpatient Clinic or admitted to the Rehabilitation Ward, Maharaj Nakorn Chiang Mai Hospital, Chiang Mai between April and May 2004. Sixty-one SCI persons had completed a self-report measure with mean age of 36.6 years and mean duration after SCI of 48.5 months. They were divided into 2 groups-those with injury more than 6 months and those within last 6 months after injury, and were compared in regard to acceptance of disability. Self-efficacy had positive correlation while depression and anxiety were negatively correlated with acceptance of disability (r=.511, -.488,-.456, p<0.01). Sex, educational level, status, severity, duration after SCI and age had no significant correlation with acceptance of disability. In addition, SCI persons who had duration after SCI of more than 6 months reported more acceptance of disability than those being SCI for less than 6 months, though not to the point of reaching the statistical significance. In conclusion, this study shows that self-efficacy and emotional status are correlated with acceptance of disability. SCI persons will be able to adjust to their disability more easily if social learning and emotional support are emphasized. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 67-70